Not Your Father’s Faculty Bibliography: Making University Scholarly Output Shine - Otto, Ryan; Hoeppner, Athena (My University, 2016)
Academics have long sought to promote their creative and scholarly output. Many university departments publish partial bibliographies of faculty scholarship, maintained by department staff and hosted on department web pages. Libraries bring together data sources, metadata skills, and tools to streamline the work, centralize the disparate bibliographies, and increase the discoverability and exposure of faculty scholarship. The presenters undertook to create a unified bibliography of scholarship authored by University of Central Florida faculty since 1978. The project team identified potential sources for metadata about faculty publications, ultimately choosing Web of Science (WoS) as a starting point. The WoS data presented problems and raised questions about department and individual name changes, authority control, and inclusiveness. The project lead parsed and normalized the data in Excel, and used Microsoft Access to establish authority control. The resulting dataset was loaded into EBSCO Discovery System as a local collection. EDS search results show an icon for UCF-authored papers and offers a filter to show just UCF papers. The project leader, now the IR manager for Kansas State University, is developing methods to load metadata-only IR records. Once loaded, the IR will serve as the platform for the faculty bibliography with links to full text on publisher sites. The poster will graphically present the steps involved in creating the bibliography; options for representing the bibliography in the IR, websites, and discovery systems; and the outcome of highlighting faculty works in EDS. An on-site laptop will allow hands-on interactions with a project demonstration.
Citation: Otto, R., Hoeppner, A. (2016). Not Your Father’s Faculty Bibliography: Making University Scholarly Output Shine. Poster session presented at the Annual Conference of the American Library Association, Orlando, FL.
Keywords: Scholarly Communications; Institutional Repositories; Metadata; Bibliographic Data; Faculty; Discovery Systems